Pelatihan Pijat Anak Bagi Orang Tua Dan Guru Anak Usia Dini - Norlaila, Norlaila; Syahkurnia, Alysbed; Wahyuni, Sri (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program carries the theme "Early Childhood Massage Training for Parents and Early Childhood Educators" with the aim of enhancing the understanding and skills of parents and teachers in providing positive touch through massage techniques for young children. The training is designed to provide practical guidance, addressing key aspects such as understanding the concept of early childhood massage, applying appropriate massage techniques, and the importance of positive touch interactions in the educational environment.Through implementation methods involving practical demonstrations and interactive discussions, participants are expected to integrate these massage skills into children's daily care routines. Monitoring and evaluation will be conducted to assess changes in participants' knowledge and practices, as well as the impact on early childhood development.The expected outcomes include improved massage skills among participants, strengthened emotional bonds between parents and children, enhanced development across six aspects of early childhood growth, and the creation of an educational environment that supports children's optimal development. Dissemination of the training results is expected to contribute positively to supporting early childhood well-being and raising public awareness of the importance of positive touch in shaping character and promoting the growth and development of young children.